2021
DOI: 10.1002/jcc.26773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mussel‐inspired co‐deposition of 2‐hydroxymethyl methacrylate and poly (2‐methoxyethyl acrylate) on the hydrophilicity and binding tendency of common hemodialysis membranes: Molecular dynamics simulations and molecular docking studies

Abstract: Despite advances in the field, hemoincompatibility remains a critical issue for hemodialysis (HD) as interactions between various human blood constituents and the polymeric structure of HD membranes results in complications such as activation of immune system cascades. Adding hydrophilic polymer structures to the membranes is one modification approach that can decrease the extent of protein adsorption. This study conducted molecular dynamics (MD) simulations to understand the interactions between three human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…We have previously reported an identical approach for studying 2‐hydroxymethyl methacrylate (HEMA) and poly (2‐methoxyethyl acrylate) (PMEA) interacting with FB residue. [ 46 ] PAN had a higher affinity of −7.1 kcal mole −1 compared to CTA of −4.3 kcal mole −1 . Based on the X‐ray crystallographic structure, PAN interacted with Ile290, Ala291, Ala261, Leu260, Leu238, leu219, Phe211, and Arg218 from HSA protein and the hydrogen bond formation was seen with Arg257, Tyr257, ser287, and Lys199 residues, as shown in Figure 6a.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously reported an identical approach for studying 2‐hydroxymethyl methacrylate (HEMA) and poly (2‐methoxyethyl acrylate) (PMEA) interacting with FB residue. [ 46 ] PAN had a higher affinity of −7.1 kcal mole −1 compared to CTA of −4.3 kcal mole −1 . Based on the X‐ray crystallographic structure, PAN interacted with Ile290, Ala291, Ala261, Leu260, Leu238, leu219, Phe211, and Arg218 from HSA protein and the hydrogen bond formation was seen with Arg257, Tyr257, ser287, and Lys199 residues, as shown in Figure 6a.…”
Section: Resultsmentioning
confidence: 96%
“…CTA and PAN were selected as the ligands (polymeric structure). [ 46 ] Aforesaid ligands were created with ChemDraw. [ 47 ] Energy minimization was performed for the structure using Chem3D Ultra (Version 8.0) software.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with in silico computer simulations showing that minimal binding energy corresponds to better binding. [30][31][32] In this experiment, it was found that the binding energy of RIF with silicone was lower than that of the other two drugs, resulting in a higher drug loading on the silicone surface, which is further discussed in section "Interaction study of antibiotic drugs and silicone tubes via molecular docking." CDM exhibited the lowest amount of drug loading into silicone tubes after swelling.…”
Section: Drug Loading After Antibiotic Impregnation and Spray Coatingmentioning
confidence: 87%
“…In vitro clinical assessments reflected better immune system response and lower inflammatory biomarker secretion after the addition of zwitterionic structure [40]. Our research group has focused on interaction profiles and modification of polymeric membranes experimentally and computationally [1, 9,11,[37][38][39][40]. We have also reviewed the most recent theories in the field of hemocompatibility improvement [12].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has focused on interaction profiles and modification of polymeric membranes experimentally and computationally [ 1 , 9 , 11 , 36 , 37 , 38 , 39 ]. We have also reviewed the most recent theories in the field of hemocompatibility improvement [ 3 ].…”
Section: Introductionmentioning
confidence: 99%